The methodological meaning of the concept of the culture of National Liberation - Subačius, Paulius (Lietuvos istorijos studijos, 1997)
The main task of this text is to prove two socio-cultural concepts: the culture of accumulation of the national and the culture of national liberation. These concepts are meant to define in all complexity the changes of rhetorical and ideological configurations of fictive literature and social communication of the XIX century in Lithuania. These theoretical constructions have developed after analysing the images of national identity in the Lithuanian poetical texts of the second half of the XIX century. The distinction between the culture of accumulation of the national and the culture of national liberation is presupposed by the opposition of static and dynamics - coming from different interpretations of the model - social reforms and authorities, and person and community. The proposed socio-cultural concepts allow a new systematization of cultural and psychological innovative metamorphoses of national idea, openness to nationalism, and the transformations it induced in the XIX century in Lithuania. The concepts are used to differentiate most general changes in culture, psychology, and awareness and, therefore, particular names or texts cannot be attributed to either. In the works of Antanas Baranauskas we can already find all the main elements of the culture of national liberation. Simonas Daukantas - in the structure discussed - must be seen as the one who carried out the maximal programme of accumulation of the national and the legitimation of the nation.